2020
DOI: 10.1111/jipb.12975
|View full text |Cite
|
Sign up to set email alerts
|

The epidermis‐specific cyclin CYCP3;1 is involved in the excess brassinosteroid signaling‐inhibited root meristem cell division

Abstract: Cell division is precisely regulated and highly tissue-specific; studies have suggested that diverse signals in the epidermis, especially the epidermal brassinosteroids (BRs), can regulate root growth. However, the underlying molecular mechanisms that integrate hormonal cues such as BR signaling with other endogenous, tissue-specific developmental programs to regulate epidermal cell proliferation remain unclear. In this study, we used molecular and biochemical approaches, microscopic imaging and genetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The cell cycle is a regulatory network composed of a series of cell-cycle-related regulatory genes, in which cyclins are involved in the whole process, especially cell division. In this study, although all cyclins were found to have at least one cyclin box, only CYCU;1 had the CD20558 structural domain through CDD prediction (Table 1), and it contained Y(L/A)(E/A)RI(F/A)(R/K)(Y/F) and (N/S)VHRLL(V/I)T motifs [29,41]. In Arabidopsis, CYCPs may be involved in cell division, cell differentiation, and the nutritional status of the cell by interacting with CDKA1 [42].…”
Section: Cyclins Play a Role In Cell Divisionmentioning
confidence: 67%
“…The cell cycle is a regulatory network composed of a series of cell-cycle-related regulatory genes, in which cyclins are involved in the whole process, especially cell division. In this study, although all cyclins were found to have at least one cyclin box, only CYCU;1 had the CD20558 structural domain through CDD prediction (Table 1), and it contained Y(L/A)(E/A)RI(F/A)(R/K)(Y/F) and (N/S)VHRLL(V/I)T motifs [29,41]. In Arabidopsis, CYCPs may be involved in cell division, cell differentiation, and the nutritional status of the cell by interacting with CDKA1 [42].…”
Section: Cyclins Play a Role In Cell Divisionmentioning
confidence: 67%
“…Model 1 includes genes involved in extracellular region, cell wall biosynthesis and lipid metabolism GO categories, implying the leaf base mainly involves growth related transcripts that accumulate at higher levels in leaf base than tip. For example, cycp3;1 , promotes cell division at the G2-M duration [ 24 ] and the expansin EXP16 is involved in cell wall expansion [ 25 ]. In contrast to this, a relatively high number of genes involved in photosynthesis related processes were highest expressed in the tip of the leaf (model 2), such as photosynthetic electron transport, chlorophyll binding, light signaling, with related genes, including OHP , OHP2 which are functionally lined to photosystem II biogenesis [ 26 ], and the early light-induced protein ELIP2 [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 20 genes were involved in cell growth and flower development. Examples for the cell growth: AC58 plays an important role in cell shape determination and cell division [57]; CYCP3-1 can regulate meristem cell division and lateral root development [58]; and MIZ1 participates in lateral root development [59]. For flower development, AP1 and AMP1 are involved in flower development [60,61]; TKPR2 is involved in pollen exine formation [62]; and HAT is essential for plant growth and development, especially in post-embryonic development [63].…”
Section: Discussionmentioning
confidence: 99%